PENINGKATAN PEMBELIAN IMPULSIF PRODUK FESYEN DI E-MARKETPLANCE MELALUI FLASH SALES, OCR DAN NILAI HEDONIS - Paramita, Cempaka; Suryaningsih, Ika Barokah; Eksanti, Eksanti (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2024)
This study is conducted to examine the role of flash sales, OCR (Online Customer Review), and hedonic value in increasing impulse buying especially for the fashion products sold in the Indonesian e-marketplaces. This research is quantitative explanatory research and the primary data was obtained from an online survey with the sample consisted of 234 respondents taken by applying purposive sampling method.  Data were analyzed using analysis of multiple linear regression. The results of this study prove that flash sales, OCR, and hedonic value have positive and significant effect on the impulse buying of fashion products in e-marketplace. These results imply that to increase consumer’s impulse buying toward fashion products, the marketers or sellers in the e-marketplace should make effective marketing strategy by conducting frequent flash sales while stimulating positive OCR and hedonic value.